Evaluation of day 5 versus day 6 blastocyst biopsy in preimplantation genetic testing: clinical and neonatal outcomes - Li, Zhiming; Fang, Xiaowu; Cheng, Lizi; Ou, Zhanhui; Huo, Junye; Yu, Wenjuan; Li, Jieliang; Ke, Wanna; Wu, Jiaqi; Lin, Xiufeng; Wen, Xiaojun (Frontiers in Endocrinology, 2025)
BackgroundPreimplantation genetic testing (PGT) has emerged as a pivotal technique in assisted reproductive technology for enhancing success rates by identifying euploid embryos prior to transfer. The optimal timing for blastocyst biopsy during PGT remains controversial, with conflicting evidence regarding the clinical outcomes of day 5 (D5) versus day 6 (D6) biopsies, as well as neonatal and perinatal outcomes.MethodsThis study involved a retrospective analysis of 3,647 biopsied blastocysts and 673 PGT-frozen embryo transfer (FET) cycles conducted at Zhongshan Boai Hospital between May 2019 and September 2024. Patients were categorized into D5 and D6 biopsy groups. The study comprised three components: (1) a comparison of chromosomal euploidy, mosaicism, and aneuploidy rates between the two groups, along with an assessment of clinical, neonatal, and perinatal outcomes in PGT-FET cycles; (2) stratification based on embryo quality to compare clinical, neonatal, and perinatal outcomes in PGT-FET cycles between the two groups; and (3) stratification according to maternal age to compare clinical, neonatal, and perinatal outcomes in PGT-FET cycles between the two groups.ResultsThe euploidy rate was significantly higher in D5 blastocysts compared to D6 blastocysts (47.53% vs. 32.38%, p < 0.01). In the PGT-FET cycles, the live birth rate in the D5 biopsy group was significantly higher than that in the D6 biopsy group (56.11% vs. 48.38%, p = 0.046); however, there were no significant differences in the clinical pregnancy rate, miscarriage rate, or neonatal outcome. Stratification by embryo quality revealed no significant differences in clinical pregnancy, live birth, or miscarriage rates for blastocysts of the same quality grade between the D5 and D6 biopsy groups. In the D5 biopsy group, variations in embryo quality did not affect clinical outcomes, whereas in the D6 biopsy group, high-quality blastocysts were associated with improved pregnancy and live birth rates. Age-stratified analysis showed similar clinical outcomes for PGT-FET in the D5 and D6 biopsy groups across different age groups.ConclusionCompared to D6, D5 biopsied blastocysts demonstrated higher euploidy and live birth rates. Therefore, it is recommended to prioritize biopsy at D5 and to thaw blastocysts at D5 for transfer to achieve better clinical pregnancy and neonatal outcomes.